2001
DOI: 10.1093/embo-reports/kve208
|View full text |Cite
|
Sign up to set email alerts
|

Irresistible IRES

Abstract: Studies on the control of eukaryotic translation initiation by a cap-independent recruitment of the 40S ribosomal subunit to internal messenger RNA sequences called internal ribosome entry sites (IRESs) have shown that these sequence elements are present in a growing list of viral and cellular RNAs. Here we discuss their prevalence, mechanisms whereby they may function and their uses in regulating gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
195
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(198 citation statements)
references
References 55 publications
1
195
0
2
Order By: Relevance
“…The cytoplasmic relocalization of hnRNP A1 after rhinovirus infection may therefore also be dependent on the p38 MAP kinase pathway as it is during stress conditions (van der Houven van Oordt et al, 2003). Numerous reports have demonstrated that IRES elements have important functions in the viral life cycle, mostly to ensure efficient viral translation when components of the host translation machinery are limited due to virus-induced modifications or host-induced antiviral responses, such as the phosphorylation of eukaryotic initiation factor 2␣ (Hellen and Sarnow, 2001;Vagner et al, 2001). However, no evidence exists to support a direct positive influence on virus IRES-mediated translation after infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasmic relocalization of hnRNP A1 after rhinovirus infection may therefore also be dependent on the p38 MAP kinase pathway as it is during stress conditions (van der Houven van Oordt et al, 2003). Numerous reports have demonstrated that IRES elements have important functions in the viral life cycle, mostly to ensure efficient viral translation when components of the host translation machinery are limited due to virus-induced modifications or host-induced antiviral responses, such as the phosphorylation of eukaryotic initiation factor 2␣ (Hellen and Sarnow, 2001;Vagner et al, 2001). However, no evidence exists to support a direct positive influence on virus IRES-mediated translation after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the hnRNP family, hnRNP K and hnRNP E1 silence translation of the 15-lipoxygenase (LOX) mRNA in immature erythroid precursor cells (Ostareck et al, 1997). Several hnRNPs, including A1, C1/C2, E1/E2, I (PTB), and L, are independently involved in the translational control of specific mRNAs containing internal ribosome entry sites (IRESs) through a capindependent mechanism (for review, see Vagner et al, 2001;Bonnal et al, 2003;Komar and Hatzoglou, 2005). These hnRNP proteins constitute IRES trans-acting factors (ITAFs) that modulate the activity of IRES sequences generally present in the 5Ј untranslated region (UTR) of several viral and cellular mRNAs (Spriggs et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism regulating the expression of the p53 isoforms remains unknown. Internal ribosome entry site (IRES)-mediated translation, where the ribosome is directly recruited to a site within the 5 0 -untranslated region (5 0 UTR) of the mRNA, is the most important mode of alternative translation initiation of eukaryotic mRNAs (Vagner et al, 2001). IRES-mediated translation has been demonstrated in the picornavirus RNAs and in several cellular mRNAs (IRES database, http://www.rangueil.inserm.fr/iresdatabase).…”
Section: Introductionmentioning
confidence: 99%
“…5 Another approach is based on the use of internal ribosome entry sites (IRES), structural RNA elements that allow the translation machinery to be recruited within the mRNA, while the dominant pathway of translation initiation recruits ribosomes on the mRNA capped 5 0 end. 6,7 IRESs can therefore be used to design expression cassettes coding for several genes from a single transcription unit. 5,8 Such genes encoded by the same mRNA are called 'cistrons' and the corresponding mRNA is 'bi-or multicistronic.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, several IRESs with distinct features and properties have been described in cellular mRNAs. 7,13 Several of them are shorter than the EMCV IRES and more flexible with regards to the distance between the IRES and the initiation codon. 14 These cellular IRESs have often been reported as having a lower activity than the EMCV IRES in cell transfection assays.…”
Section: Introductionmentioning
confidence: 99%